The Interdisciplinary Role Of Nursing, Social Work, General Practitioners, Radiology Technicians, And Health Service Management In Enhancing Early Detection And Management Of Stroke Patients (The Review of Diabetic Studies, 2025)
Stroke is a leading global cause of death and severe long-term disability and requires a thorough interdisciplinary response for best possible outcomes. This peer-reviewed overview reviews the coordinated roles of nursing, social work, general practitioners, radiology technicians, and health service management in early detection and management of stroke. Nursing delivers vigilant observation and time-critical interventions; social work covers psychosocial support and accessibility of resources; general practitioners provide early recognition, continuity, and management of risk factors; radiology technicians facilitate diagnostic imaging for therapeutic purposes sooner rather than later; and health service managers implement system-level coordination and resource alignment. Research proves that interdisciplinary practice minimizes delay in therapy, increases functional output, and optimizes patient satisfaction. Despite that, information barriers, role confusion, and resource constraints continue. Enhanced interdisciplinary protocols, interprofessional education, and aligned care tracks are needed to implement best practice. Whole-of-system models have the capacity to minimize stroke mortality by 30% while maximizing quality-adjusted life years for survivors.